CGF-HLC-I repaired the bone defect repair of the rabbits mandible through tight junction pathway - Mao, Yalin; Hu, Miaoling; Chen, Li; Chen, Xiao; Liu, Maohua; Zhang, Menglian; Nie, Minhai; Liu, Xuqian (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The human-like collagen I (HLC-I) combined concentrated growth factors (CGF) was used to construct CGF-HLC-I composite biomaterials to repair the critical bone defect disease model of rabbit mandible. This study researched the repair mechanism of CGF-HLC-I/Bio-Oss in rabbit mandibular critical bone defect was to provide a new treatment direction for clinical bone defect repair. Methods: The optimal concentration of HLC-I was selected in this study. 9 New Zealand white rabbits were selected and divided into 3 groups, normal control group, Bio-Gide/Bio-Oss and CGF-0.75%HLC-I/Bio-Oss group (n=3, each group). CGF-0.75%HLC-I/Bio-Oss and Bio-Gide/Bio-Oss were implanted into rabbit mandibles, and X-ray, Micro-CT, HE and Masson staining, immunohistochemical staining and biomechanical testing were performed at 4, 8 and 12 weeks (W) after surgery. A total of 131 proteins with different expression levels were screened from group C and group B. The repair mechanism was studied by bioinformatics experiments. Results: The results showed that as the material degraded, the rate of new bone formation in the CGF-0.75% HLC-I/Bio-Oss group was better than that the control group. The biomechanical test showed that the compressive strength and elastic modulus of the CGF-0.75%HLC-I/Bio-Oss group were higher than those of the control group. HE and Masson staining showed that the bone continuity or maturity of the CGF-0.75%HLC-I/Bio-Oss group was better than that of the control group. Immunohistochemical staining showed significantly higher bone morphogenetic protein 2 (BMP2)and Runt-related transcription factor (RUNX2) in the CGF-0.75%HLC-I/Bio-Oss group than the control group at 8 and 12 W and the difference gradually decreased with time. There were 131 differentially expressed proteins (DEPs) in the B and C groups, containing 95 up-regulated proteins and 36 down-regulated proteins. KEGG database enrichment analysis results: actinin alpha 1 (ACTN1) and myosin heavy-Chain 9 (MYH9) are the main potential differential proteins related to osteogenesis, and they are enriched in the TJs pathway. Conclusion: CGF-0.75%HLC-I/Bio-Oss materials can promote new bone formation, providing new ideas for the application of bone tissue engineering scaffold materials in oral clinics.